2013
DOI: 10.1002/aqc.2331
|View full text |Cite
|
Sign up to set email alerts
|

Survival of rockhopper penguins in times of global climate change

Abstract: 1. Anthropogenic changes in the marine environment and global climate change have led to population declines in several seabird species worldwide. Rockhopper penguins (Eudyptes chrysocome and Eudyptes moseleyi) have experienced a dramatic population decline, potentially linked to increasing sea surface temperatures (SST). Among Southern Ocean diving seabirds, rockhopper penguins typically occupy a low trophic level, and might therefore be expected to mirror climate-driven bottom-up changes to the food web sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 80 publications
4
33
0
Order By: Relevance
“…The potential negative effects of warm pre-laying SST and exceptionally low over-winter SST on subsequent ERP diet quality suggest a quadratic relationship between SST and diet quality. Similarly, Dehnhard et al (2013) found a quadratic relationship between adult survival of SRP in the southwest Atlantic and SST in a 3-month period overlapping moult. Décima et al (2013) found that an inter-annual increase in SST of c.3 °C was associated with an increase of c.2 ‰ in the baseline δ 15 N values of zooplankton in the California Current Ecosystem.…”
Section: Discussionmentioning
confidence: 75%
“…The potential negative effects of warm pre-laying SST and exceptionally low over-winter SST on subsequent ERP diet quality suggest a quadratic relationship between SST and diet quality. Similarly, Dehnhard et al (2013) found a quadratic relationship between adult survival of SRP in the southwest Atlantic and SST in a 3-month period overlapping moult. Décima et al (2013) found that an inter-annual increase in SST of c.3 °C was associated with an increase of c.2 ‰ in the baseline δ 15 N values of zooplankton in the California Current Ecosystem.…”
Section: Discussionmentioning
confidence: 75%
“…The same phenomenon, to a lesser extent, has been observed in SRP during the chick-rearing period (Dehnhard et al 2016). Furthermore, it could be shown that lower SST increased not only the likelihood of SRP individual survival over the winter months (Raya Rey et al 2007;Dehnhard et al 2013) but also individual body mass at the onset of the reproduction period (Dehnhard et al 2015a). In turn, the latter resulted in earlier egg-laying dates with increased clutch masses (Dehnhard et al 2015b) and an overall higher breeding success (Crawford et al 2008).…”
Section: Trip Duration and Sstmentioning
confidence: 71%
“…Thus, it can be expected that their preferred foraging areas are also influenced by the prevailing oceanographic conditions . Studies have shown a link between SST and overwintering survival of SRP at both, the Falklands/Malvinas archipelago and Staten Island (Raya Rey et al 2007;Dehnhard et al 2013). In particular, extreme shifts in SST had negative effects on the survival of adults at both sites.…”
Section: Introductionmentioning
confidence: 99%
“…The decline that was occurring for the rockhopper penguins at the Antipodes Islands appears to have lessened and possibly halted, as is the case with other eastern rockhopper populations (Baylis, Wolfaardt, Crofts, Pistorius, & Ratcliffe, ; Dehnhard et al, ; Kirkwood et al, ; Morrison et al, ; Oehler et al, ). The widespread and largely simultaneous declines of rockhopper penguin populations throughout their range were thought to be the result of a single shared cause.…”
Section: Discussionmentioning
confidence: 95%
“…Climate change has been predicted and observed to significantly alter the world's environment and impact all aspects of the life cycle of marine species (life history traits, phenology, movement, Solomon et al, ). These changes are known to affect penguin population parameters and size (Ainley et al, ; Ainley & Blight, ; Dehnhard et al, ; Demongin, Poisbleau, Strange, & Quillfeldt, ; Morrison, Battley, Sagar, & Thompson, ; Parmesan, ; Parmesan & Yohe, ; Trathan et al, ; Walther et al, ). Climate change is altering weather patterns around the globe, including increasing the frequency and severity of storms, significantly increasing precipitation in some areas, bringing flooding and landslides (Coumou & Rahmstorf, ).…”
Section: Introductionmentioning
confidence: 99%